(untitled) (American Journal of Business Management, Economics and Banking, 2024)
In this article, the system of human capital development has its own socio-economic orientation. In addition to the sum of the participants and their interactions, the human capital development system includes the environment, certain integration mechanisms that develop the interaction of the participants, and the adaptation mechanism that serves as the basis for the system’s stability and self-development.